Contractile recovery from acidosis in toad ventricle is independent of intracellular pH and relies upon Ca2+ influx - Salas, Margarita Ana (2006)
Hypercapnic acidosis produces a negative inotropic effect on myocardial contractility followed by a partial recovery that occurs in spite of the persistent extracellular acidosis. The underlying mechanisms of this recovery are far from understood, especially in those species in which excitation-contraction coupling differs from that of the mammalian heart. The main goal of the present experiments was to obtain a better understanding of these mechanisms in the toad heart. Hypercapnic acidosis, induced by switching from a bicarbonate-buffered solution equilibrated with 5% CO2 to the same solution equilibrated with 12% CO2, evoked a decrease in contractility followed by a recovery that reached values higher than controls after 30 min of continued acidosis. This contractile pattern was associated with an initial decrease in intracellular pH (pHi) that recovered to control values in spite of the persistent extracellular acidosis. Blockade of the Na+/H+ exchanger (NHE) with cariporide (5 μmol l-1) produced a complete inhibition of pHi restitution, without affecting the mechanical recovery. Hypercapnic acidosis also produced a gradual increase of diastolic and peak Ca2+i transient values, which occurred immediately after the acidosis was settled and persisted during the mechanical recovery phase. Inhibition of Ca2+ influx through the reverse mode of the Na+/Ca2+ exchanger (NCX) by KB-R (1 μmol l-1 for myocytes and 20 μmol l-1 for ventricular strips), or of L-type Ca2+ channels by nifedipine (0.5 μmol l-1), completely abolished the mechanical recovery. Acidosis also produced an increase in the action potential duration. This prolongation persisted throughout the acidosis period. Our results show that in toad ventricular myocardium, acidosis produces a decrease in contractility, due to a decrease in Ca2+ myofilament responsiveness, followed by a contractile recovery, which is independent of pHi recovery and relies on an increase in the influx of Ca2+. The results further indicate that both the reverse mode NCX and the L-type Ca2+ channels, appear to be involved in the increase in intracellular Ca2+ concentration that mediates the contractile recovery from acidosis.